THE ROLE OF MNEMONICS IN TEACHING CHILDREN IN PRIMARY CLASSES - Shukurullayeva Munisa Maxsudjon qizi,; Umarova Ziyoda, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
This article examines the significant role of mnemonic techniques in teaching children in primary classes. Mnemonics are widely recognized as effective cognitive tools that facilitate memory retention and recall by organizing information into meaningful patterns, associations, and visual representations. The study provides a comprehensive overview of different types of mnemonics, including acronyms, acrostics, rhymes, songs, visual imagery, and story-based techniques, and analyzes their practical application in classroom environments.Furthermore, the article explores how mnemonic strategies contribute to the cognitive development of young learners by enhancing their memory capacity, attention span, and problem-solving skills. It also highlights the emotional and motivational benefits, such as increased engagement, improved self-confidence, and reduced anxiety during the learning process. Special attention is given to the adaptability of mnemonic methods for diverse learners with different learning styles.In addition, the article discusses certain limitations of mnemonic usage, emphasizing that these techniques should complement, rather than replace, deep conceptual understanding. The findings suggest that when integrated effectively into teaching practices, mnemonics can significantly improve the quality and efficiency of primary education.